2022
DOI: 10.3390/ma16010390
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic and Mechanistic Investigation of Stress-Assisted Microbiologically Influenced Corrosion of X80 Steel in Near-Neutral Solutions

Abstract: The behavior and mechanisms of the stress-assisted microbiologically influenced corrosion (MIC) of X80 pipeline steel induced by sulfate-reducing bacteria (SRB) were investigated using focused ion beam-scanning electron microscopy (FIB). Electrochemical results show that SRB and stress have a synergistic effect on the corrosion of X80 steel. SRB accelerated the transformation of Fe3O4 into iron-sulfur compounds and may have caused the film breakage of X80 steel products. The obtained FIB results provide direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…In recent years, EET has been recognized as a prevalent mechanism of MIC. It involves the entry of electrons generated from metal oxidation into the cytoplasm and completes the respiratory processes of microorganisms [13][14][15][16]. In addition, an increasing number of research studies suggested that microorganisms could utilize alloying compounds within passive film of stainless steel as alternative electron acceptors, which led to the damage of the passive film [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, EET has been recognized as a prevalent mechanism of MIC. It involves the entry of electrons generated from metal oxidation into the cytoplasm and completes the respiratory processes of microorganisms [13][14][15][16]. In addition, an increasing number of research studies suggested that microorganisms could utilize alloying compounds within passive film of stainless steel as alternative electron acceptors, which led to the damage of the passive film [17,18].…”
Section: Introductionmentioning
confidence: 99%